2018
DOI: 10.1186/s12936-018-2276-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigating insecticide resistance and knock-down resistance (kdr) mutation in Dielmo, Senegal, an area under long lasting insecticidal-treated nets universal coverage for 10 years

Abstract: BackgroundThe use of insecticides, through indoor residual spraying and long-lasting insecticide-treated nets (LLINs), is essential to control malaria vectors. However, the sustainability of these tools is challenged by the spread of insecticide resistance in Anopheles mosquitoes. This study was conducted to assess the susceptibility to insecticides and to determine the resistance mechanisms in malaria vectors in Dielmo, a rural area of western Senegal where LLINs were introduced a decade ago.MethodsCDC bottle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 51 publications
6
23
4
Order By: Relevance
“…This hypothesis should be investigated in the future. These results are in line with those of Thiaw et al [31] and Ahoua et al [32], who found no correlation between the kdr mutation and the phenotypic alive or dead phenotypic respectively in An. arabiensis and An.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This hypothesis should be investigated in the future. These results are in line with those of Thiaw et al [31] and Ahoua et al [32], who found no correlation between the kdr mutation and the phenotypic alive or dead phenotypic respectively in An. arabiensis and An.…”
Section: Discussionsupporting
confidence: 93%
“…Previous studies have reported resistance only to DDT and pyrethroids in southeastern and central Senegal where LLIN use is high, [30,31]. However, unlike previous studies conducted in Senegal, this study shows that vectors are resistant to almost all pyrethroids and bendiocarb.…”
Section: Discussioncontrasting
confidence: 82%
“…Previous studies have reported resistance only to DDT and pyrethroids in southeastern and central Senegal where LLIN use is high, [30,31]. However, unlike previous studies conducted in Senegal, this study shows that vectors are resistant to almost all tested pyrethroids and bendiocarb.…”
Section: Discussioncontrasting
confidence: 84%
“…gambiae s.l. to insecticides have revealed, often at different levels, a phenotypic resistance to DDT and to pyrethroids in most parts of Senegal, except in the north and extreme southeast [13,31,30]. The aims of this study were to update the current status of insecticide resistance among An.…”
Section: Introductionmentioning
confidence: 99%
“…The adults An. arabiensis issued from a larval population carry kdr alleles despite the fact that this was not associated with resistance to pyrethroids [33], while no data regarding An. funestus is available, although its resistance to lambda-cyhalothrin has been recorded elsewhere in Senegal [34].…”
Section: Discussionmentioning
confidence: 99%